Trends of the second measles vaccine (MCV2) over time after its launch as part of routine immunization in Nigeria: a brief research report - Sato, Ryoko (Frontiers in Public Health, 2024)
Nigeria has one of the highest measles burdens and lowest vaccination coverage in the world. Geographical disparity in the coverage has also been persistent. Between 2019 and 2021, the Nigerian government introduced the 2nd dose of measles-containing vaccine (MCV2) with into the routine immunization (RI). This study evaluated the trends of the MCV2 coverage over time across geographical zones. The monthly data on the MCV2 coverage from District health Information Software (DHIS2) for all the health facilities in Nigeria were aggregated by the geopolitical zone and the trend of the MCV2 coverage was analyzed over time. The MCV2 coverage in each zone was approximately 20% when MCV2 program was launched. One year after the launch (year 1), the MCV2 coverage was higher in northern zones (35 to 42%) compared with southern zones (22 to 31%). Similarly at year 2.5, the MCV2 coverage was 38 to 46% in northern zones while it was 23 to 37% in southern zones. The introduction of MCV2 as part of RI schedule potentially narrows down the health inequity in Nigeria.